Analysis of Factors Inhibiting Students in Speaking English as a Foreign Language: Qualitative Study in Classes VIII and IX at Mts Darul Falah Cibungur - Nurfadhlina Abdul Hali; Siti Hadiaty Yuningsih; Nurnisaa binti Abdullah Suhaimi (Research Collaboration Community (RCC), 2024)
This research investigates the factors that hinder students from speaking English as a foreign language in the classroom. Through qualitative research methods involving students and teachers, the findings show that there are two main factors that influence students' speaking abilities, namely affective factors and cognitive factors. Affective factors include eleven subfactors such as shyness, nervousness, and lack of self-confidence, while cognitive factors involve problems with grammar, pronunciation, and vocabulary. In addition, the influence of teachers and peers also has a significant role in overcoming or exacerbating these factors. This research has implications for designing more effective speaking learning and a supportive environment for students in overcoming speaking barriers.